25 gauge technology in vitrectomy: pro and con - Robaszkiewicz, Jacek; Wójcik, Ewa (Klinika Oczna / Acta Ophthalmologica Polonica, 2006)
In the article authors present new technology of performing vitrectomy. During the surgery we used tools twice lesser in diameter than in traditional method. Main indications for its use are: macular hole (stage II, III and IV), idiopatic epiretinal membrane (cellophane maculopathy, macular pucker), secondary epiretinal membrane, vitreotraction macular syndrome, endophthalmitis, haemophthalmia, traction retinal detachment, diabetic macular edema, proliferative diabetic retinopathy, giant retinal tears, radial optic neurotomy, sheathotomy. At present, the best alternative is one day surgery.